Real-Time G-Protein-Coupled Receptor Imaging to Understand and Quantify Receptor Dynamics - María S. Aymerich; J. López-Azcárate; J. Bonaventura; G. Navarro; D. Fernández-Suárez; V. Casadó; F. Mayor; C. Lluís; M. Valencia; J. Artieda; Rafael Franco (The Scientific World Journal, 2011)
Understanding the trafficking of G-protein-coupled receptors (GPCRs) and their regulation by agonists and antagonists is fundamental to develop more effective drugs. Optical methods using fluorescent-tagged receptors and spinning disk confocal microscopy are useful tools to investigate membrane receptor dynamics in living cells. The aim of this study was to develop a method to characterize receptor dynamics using this system which offers the advantage of very fast image acquisition with minimal cell perturbation. However, in short-term assays photobleaching was still a problem. Thus, we developed a procedure to perform a photobleaching-corrected image analysis. A study of short-term dynamics of the long isoform of the dopamine type 2 receptor revealed an agonist-induced increase in the mobile fraction of receptors with a rate of movement of 0.08 μm/s For long-term assays, the ratio between the relative fluorescence intensity at the cell surface versus that in the intracellular compartment indicated that receptor internalization only occurred in cells co-expressing G protein-coupled receptor kinase 2. These results indicate that the lateral movement of receptors and receptor internalization are not directly coupled. Thus, we believe that live imaging of GPCRs using spinning disk confocal image analysis constitutes a powerful tool to study of receptor dynamics.